Teach Programming: Development of an educational game for teaching programming (Research, Society and Development, 2025)
Computing is crucial in modern society. With the growth of the field and, consequently, the demand for effective methods of teaching programming, this work developed an educational game that uses gamified elements and solid pedagogical principles to create a dynamic and motivating learning experience. The aim of this article is to present a project, developed within the scope of the extension project "Clube da Programação" at the Federal Institute of Sertão Pernambucano, which is an educational game that uses gamified elements and solid pedagogical principles. The game was implemented using Python and the Flask framework on the back-end, MongoDB as the database, and an intuitive interface in HTML, CSS, and JavaScript on the front-end. The results obtained include the development of the first version of the game, as well as supplementary pedagogical material. It is concluded that the project demonstrates great potential to contribute significantly to the teaching and learning process of programming.